Acquisition and Transfer of Values and Social Skills through a Physical Education Program Focused in the Affective Domain - Pedro Gil Madrona; Amaury Samalot-Rivera; Francis M Kozub (Desafio Singular, 2017)
The purpose of this study was to examine the effectiveness of a physical education (PE) program focused on the affective domain for 6th to 8th grade students with respect to the acquisition and transfer of social skills and values. Further, the extent that general classroom teachers and parents perceived if the learned skills where transferred to other context outside the PE class was examined in a sample of 274 students (ages 11 to 13 years old). One hundred and forty-five males (53%) and 129 females (47%) from five urban schools in Albacete Spain were studied. Three questionnaires were used (pre and post rating scales) as data collection instruments for students, teachers and parents. Results demonstrated encouraging estimates of reliability for the subscales of PE teachers' perceptions of students' values and regular education teaches perceptions with very strong values of internal consistency .82 and .93 respectively. Posttest values were slightly higher. Further, findings demonstrated positive outcomes after the intervention in teacher perceptions about students values levels (t =-8,05; p < .01), enjoyment, (t =-7.10; p < .01), fair play (t = -8.09; p < .01), social relation (t = -6.48; p < .01), good habits (t = -7.43; p < .01) and emotional control (t = -6.03; p < .01) in favor of the intervention group. These results support previous studies evidencing that integrating social skills and values intervention in the PE class increase students' development in the affective domain.